Design Patterns for Image Processing Algorithm Development on FPGAs - Gribbon, K.T.; Bailey, D.G.; Johnston, C.T. (TENCON 2005 - 2005 IEEE Region 10 Conference, 2005)
FPGAs are often used as implementation platforms for real-time image processing applications because their structure allows them to exploit spatial and temporal parallelism. Such parallelization is subject to the processing mode and hardware constraints including limited processing time, limited access to data and limited resources of the system. These constraints often force the designer to reformulate the software algorithm in the process of mapping it to hardware. To aid in the process this paper proposes the application of design patterns which embody experience and through reuse provide tools for solving particular mapping problems. Issues involved in applying design patterns in this manner are outlined and discussed.